Professionalization of Clinical Bioethics: This is the Way - Wyzynski, Daniel (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Professionalization across the field of bioethics is valuable and should be invested in by future generations of ethicists. To support this, standardization should expand beyond clinical ethics, ensuring considerations for organizational and research ethics, and encouraging membership that includes those with diverse backgrounds of education, lived experiences, and employment.